Bismuth vanadate modified glassy carbon electrode for sensitive electrochemical antibiotic detection - Nedy, Timmy Unya; Ali Rahman, Mohammad Aliff; Teo, Ellie Yi Lih; Yiu, Pang Hung; Yiu, Elisha; Zheng, Alvin Lim Teik; Andou, Yoshito (Springer Science and Business Media B.V., 2025)
This study presents the successful synthesis of bismuth vanadate (BiVO4) using a hydrothermal method and its application as a modifier on glassy carbon electrode (GCE). Fourier-transform infrared (FTIR) spectroscopy confirmed the presence of V–O stretching vibrations, while X-ray diffraction (XRD) analysis verified a pure monoclinic BiVO4 crystal structure. Morphological analysis revealed spherical BiVO4 particles, which contributed to enhanced electrochemical performance when integrated into the modified GCE. BiVO4/GCE exhibited superior electrochemical performance, as confirmed by cyclic voltammetry (CV) and differential pulse voltammetry (DPV) studies, in detecting analytes including hexacyanoferrate, tetracycline (TC), and levofloxacin (LVX). BiVO4 modification significantly boosted the performance of the electrode in terms of sensitivity, selectivity, and electron transfer kinetics. These enhancements can be attributed to BiVO4’s efficient electron transport and electrocatalytic activity. Notably, BiVO4/GCE exhibited the potential for simultaneous detection of multiple antibiotics showing its versatility for diverse electrochemical sensing applications. The limits of detection (LOD) and quantification (LOQ) for TC were 27.9 µM and 83.3 µM, respectively, while for LVX, they were 7.39 µM and 22.3 µM. Overall, these findings position BiVO4/GCE as a promising platform for advanced electrochemical detection and analysis across various fields.